The creativity of designing Batik Serumpun Melayu through Indonesian-Malaysian cultural acculturation - Pujiyanto; Hidajat, Robby; Anggriani, Swastika Dhesti; Nurul Aini; Shaari, Nazlina (Atlantis Press BV, 2021)
The occurrence of claiming the cultural results of one country makes other countries unwilling to release because they feel that the culture that other countries claim belongs to them. This condition causes the relationship between the two countries to be less harmonious. If viewed from the Malayan’s history, the two countries have the same family culture, namely the Malayan culture. This culture can be used to explore and produce a new Malayan culture, one of which is the batik, which is characterized by a Malayan family culture. “Batik Serumpun Melayu”. Data were collected through observations in several cities in the Sumatera region to Kuala Lumpur to produce the “Batik Serumpun Melayu”. The interviews were conducted with resource persons who knew the Malayan culture, as well as document data in the form of artifacts from past Malayan culture to strengthen the data. Through this research, data objects are used as a source of ideas in the creation of “Batik Serumpun Melayu”. Through the acculturation approach of Indonesian-Malaysian culture, a creative process of Design Thinking from Plattner, Meinel & Weinberg in the form of understanding, observe, point of view, ideate, prototype, and test to produce the batik “Relung Mekar Melayu” which has had Intellectual Property Right (HKI). It is hoped that the batik’s invention is expected to unite the Malayan culture, which means to unite the Indonesian-Malaysian culture in the batik “Relung Mekar Melayu” which is shared, worked together and developed together.